Agentes invisíveis e modos de produção nos primeiros anos do Workcenter of Jerzy Grotowski : Invisible agents and production ways on the first years of the Workcenter of Jerzy Grotowski - Sampaio, Daniele, 1982- (2018)
Orientador: Tatiana da Motta Lima Ramos